A weighted anisotropic variant of the Caffarelli–Kohn–Nirenberg inequality and applications. (8th March 2018) - Bahrouni, Anouar; Rădulescu, Vicenţiu D; Repovš, Dušan D
Abstract: We present a weighted version of the Caffarelli–Kohn–Nirenberg inequality in the framework of variable exponents. The combination of this inequality with a variant of the fountain theorem, yields the existence of infinitely many solutions for a class of non-homogeneous problems with Dirichlet boundary condition.